Identification of 22 Novel Motifs of the Cell Entry Fusion Glycoprotein B of Oncolytic Herpes Simplex Viruses: Sequence Analysis and Literature Review - Shi, Fang; Xin, Victoria W.; Liu, Xiao-Qin; Wang, Ying-Ying; Zhang, Ying; Cheng, Jun-Ting; Cai, Wen-Qi; Xiang, Ying; Peng, Xiao-Chun; Wang, Xianwang; Xin, Hong-Wu (Frontiers in Oncology, 2020)
Objective: Herpes simplex virus (HSV) glycoprotein B (gB) is a viral surface cell entry fusion protein. Only in recent years has the importance of gB been realized in HSV infection and oncolytic HSV (oHSV) engineering. However, the detailed molecular biology of gB is still unclear, which negatively affects the construction of effective oHSVs. Method: Here we performed a systematic comparative sequence analysis of gBs from the 9 HSV-1 and 2 HSV-2 strains, including our recently isolated new strain HSV-1-LXMW. Online software was implemented to predict gB secondary structure, motifs, and function domains. Based on an extensive literature review, a functional analysis of the predicted motifs was performed. Results: Here we reported the DNA and predicted amino acid sequences of our recently isolated HSV-1-LXMW and found that the strain is evolutionarily close to HSV-1 strains F, H129 and SC16. 22 novel motifs of HSV gB were identified for the first time. An amino acid sequence alignment of the 11 HSV strains showed that the gB motifs are conserved among HSV strains, suggesting they are functional in vivo. We further found that 14 motifs out of the 22 motifs were reported to be functional in vivo. The gB mutants and gB engineered oHSVs were summarized. Conclusion: Our identification of the 22 novel motifs shed light on HSV gB biology and provide new insights for gB engineering to improve the efficiency and safety of oHSVs.